TCM coding of PPM based modulations for Infrared WLAN's impaired by ISI - Alves, R. (2012)
In this communication we consider the use of PPM based modulation methods, such as the hybrid modulation method called Amplitude and Pulse-Position Modulation (APPM) and Overlapping Pulse-Position Modulation (OPPM) to improve the performance of infrared WLAN’s, by the use of Trellis-Coded Modulation (TCM) codes. We describe the best code search and results, which demonstrate that, even with trellis codes of moderate complexity, non-negligible coding gains can be obtained without bandwidth expansion. Monte Carlo simulations have been done to compare uncoded PPM against APPM and OPPM TCM coded systems performances, on ceiling-bounce channel models for various values of delay spread. Although our codes were derived for the AWGN channel without Inter-Symbol Interference (ISI) awareness, their behavior in multipath dispersion channels is quite effective.